Bone Density and Implant Stability in using Advanced Platelet Rich Fibrin in Immediately Loaded- Implant Assisted Mandibular Overdentures - Allah, Eman Sabry Ata; Elfatah, Fadel Elsaid ABD; Rashed, Hoda Mohamed Amin; Hassib, Mona Talaat Mohamed (Brazilian Dental Science, 2023)
Objective: The aim of this study is to determine the effect of Advanced Platelet-Rich Fibrin on bone density and implant stability in immediately loaded- implant-assisted mandibular overdentures (Split-mouth study). Material and Methods: Ten completely edentulous patients received two implants in the mandibular canine region and locator attachments were used to retain immediately loaded- implant mandibular overdentures. Each patient served in two Groups, one Group for each side. One side of the mandible received an implant with topical application of Advanced Platelet-Rich Fibrin in the implant osteotomy site (Group I) and the other site received an implant without application of Advanced platelet-rich fibrin (Group II). Each patient was examined clinically for implant stability using Osstell Mentor device and radiographically by ultra-low dose CT scan to measure bone density around the implant at baseline, three, six months, and one year. Results: There were no statistically significant differences (P>.05) in bone density and implant stability among the studied Groups during one year follow-up period. Conclusion: Advanced Platelet-Rich Fibrin has no effect on bone density and implant stability in immediately loaded implant-assisted mandibular overdenture. KEYWORDS Advanced platelet-rich fibrin; Bone density; Immediately loaded implant; Implant stability; Locator attachment; Mandibular overdentures.